2012
DOI: 10.1074/jbc.m111.325456
|View full text |Cite
|
Sign up to set email alerts
|

Phenolic Compounds Prevent Amyloid β-Protein Oligomerization and Synaptic Dysfunction by Site-specific Binding

Abstract: Background: Epidemiological evidence suggests that consumption of phenolic compounds reduce the incidence of Alzheimer disease (AD). Results: Myricetin and rosmarinic acid reduced cellular and synaptic toxicities by inhibition of amyloid ␤-protein (A␤) oligomerization. Myricetin promoted NMR changes of A␤. Conclusion: Phenolic compounds are worthy therapeutic candidates for AD. Significance: Phenolic compounds blocked early assembly processes of A␤ through differently binding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
173
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 229 publications
(182 citation statements)
references
References 54 publications
8
173
1
Order By: Relevance
“…Only several years later did structural insights emerge with respect to the residues on Aβ to which these compounds bind. 18 Very recent work by Sinha and co-workers has described the identification of lysine and arginine residues as targets for anionic "molecular tweezers" that inhibit aggregation. 19,20 In contrast to this specific interaction, other compounds that show strong inhibitory interaction are poorly characterized by experimental methods.…”
mentioning
confidence: 99%
“…Only several years later did structural insights emerge with respect to the residues on Aβ to which these compounds bind. 18 Very recent work by Sinha and co-workers has described the identification of lysine and arginine residues as targets for anionic "molecular tweezers" that inhibit aggregation. 19,20 In contrast to this specific interaction, other compounds that show strong inhibitory interaction are poorly characterized by experimental methods.…”
mentioning
confidence: 99%
“…The therapeutic efficacy of RA has been tested in both in vitro and in vivo models of AD. Previous studies have been tested the effect of RA on Ab aggregation in both in vitro and transgenic mice model of AD [41,42]. It has been reported that RA prevents Ab oligomerization under in vitro conditions and that RA prevents Ab-induced alterations of neuronal plasticity in the CA1 region of mouse hippocampus slices [41].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have been tested the effect of RA on Ab aggregation in both in vitro and transgenic mice model of AD [41,42]. It has been reported that RA prevents Ab oligomerization under in vitro conditions and that RA prevents Ab-induced alterations of neuronal plasticity in the CA1 region of mouse hippocampus slices [41]. Oral administration of RA decreased the Ab burden in the AD model transgenic mice by inhibiting the Ab aggregation pathway from Ab monomers to A11-positive oligomers and from A11-positive oligomers to Ab deposition [42].…”
Section: Discussionmentioning
confidence: 99%
“…Among natural compounds, most Aβ inhibitors present a polyphenolic core [42], including resveratrol [43], myricetin [44], curcumin [45], caffeine [46].…”
Section: Aβ Aggregation Inhibitormentioning
confidence: 99%